Pro- and Anti-Inflammatory Properties of Interleukin in Vitro: Relevance for Major Depression and Human Hippocampal Neurogenesis - Borsini, Alessandra (Int J Neuropsychopharmacol, 2020)
BACKGROUND: Although the pro-inflammatory cytokine interleukin (IL)6 has been generally regarded as “depressogenic,” recent research has started to question this assumption in light of the fact that this cytokine can also have anti-inflammatory properties. This bimodal action seems to be dependent on its concentration levels and on the concomitant presence of other pro-inflammatory cytokines. METHODS: We exposed a human hippocampal progenitor cell line, HPC0A07/03C, to cytokine levels described in depressed patients (IL6 5 pg/mL with IL1β 10 pg/mL or Macrophage Migration Inhibitory Factor (300 pg/mL) in healthy individuals (IL6 with IL1β, 1 pg/mL or Macrophage Migration Inhibitory Factor 10 pg/mL), as well as to the potentially anti-inflammatory, much higher concentrations of IL6 (50 000 pg/mL). RESULTS: Treatment with high concentrations of IL6 with IL1β or Macrophage Migration Inhibitory Factor (resembling depressed patients) decreases neurogenesis compared with low concentrations of the same cytokines (healthy individuals) and that this is mediated via production of, respectively, IL8 and IL1β in cell supernatant. Instead, treatment with very high, anti-inflammatory concentration of IL6 (50 000 pg/mL) together with high IL1β or Macrophage Migration Inhibitory Factor prevents decrease in neurogenesis and reduces both IL8 and IL1β. When high concentrations of both IL1β and Macrophage Migration Inhibitory Factor were used in co-treatment, as a model of treatment-resistant depression, we also demonstrated a reduction in neurogenesis and that this is mediated via a decrease in IL4; moreover, co-treatment with high IL1β and Macrophage Migration Inhibitory Factor and the very high concentration of IL6 prevented the reduction in neurogenesis and increased IL4. CONCLUSIONS: Our results demonstrate that IL6 can exert both pro- and anti-inflammatory (potentially antidepressant) properties, depending on its concentrations and combinations with other inflammatory cytokines.